The Relationship Between First-Trimester Aneuploidy Markers and Birth Weight - Cenk Soysal; Hatice Sari; Ozlem Erten; Ismail Biyik; Onur Ince; Yasemin Tasci; Nadi Keskin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aimed to determine the relationship between the first-trimester aneuploidy screeningma and the predicted weight at birth: Small for gestational age and large for gestational age.